Immunomodulatory Effects of Tryptophan Metabolism in the Glioma Tumor Microenvironment - Xu, Yang; Zhang, Huikai; Sun, Qian; Geng, Rongxin; Yuan, Fanen; Liu, Baohui; Chen, Qianxue (Frontiers in Immunology, 2021)
Glioma is considered to be a malignant tumor in the central nervous system. While current research on glioma treatment is advancing rapidly, there is still no breakthrough in long-term treatment. Abnormalities in the immune regulatory mechanism in the tumor microenvironment are essential to tumor cell survival. The alteration of amino acid metabolism is considered to be a sign of tumor cells, which has a significant impact on tumor cells and immune regulation mechanism in the tumor microenvironment. Despite the fact that the metabolism of tryptophan in tumors is currently discussed in the literature, in this article, we focus on reviewing the immune regulation of tryptophan metabolism in the tumor microenvironment of gliomas and analyzed possible immune targets. The objective is to identify potential targets for the treatment of glioma and improve the efficiency of immunotherapy.